Evaluation Study an Integrated Vital Sign Device by using Glucose Sensor for Auto-Capture of Biological Data - Jaya, A.K.R.A.; Kassim, A.M.; Syahid, S.; Azahar, A.H. (International Journal of Human and Technology Interaction (IJHaTI), 2019)
Nowadays, a lot of medical equipment has been integrated with the electronic device to make the medical equipment more users friendly. In this project, a device using glucose sensor to automatically capture the biological data will be develop to help the doctor to follow up the patient health information. The traditional medical equipment is to take the reading such as blood pressure, blood glucose level, temperature and etc. manually. Normally the traditional method will have many errors occur when taking the reading like parallax error or human error. Other than that, the traditional method also consumes lot of time when taking the biological data. In this project, a innovative device will be design and develop to take the biological data automatically which replace the traditional method of taking the glucose tests manually. The integrated device is expected to be designed for collecting the blood glucose data from the designed blood glucose measuring mechanism that is attached on a medical checkup chair and consequently integrate them into the personal medical database that can be transmitted through an USB device to a server. The traditional method consumes too much time from collecting sample until recording the data into the computer and human error may be occurring during recording the data. Hence, less time consume and fast action can be made by nurse and medical doctor to observe the patient current health information in order to provide the most suitable treatment to the patient from time to time.